(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
The retail industry in India has witnessed remarkable growth in recent years, with organised retail formats like D’Mart playing a pivotal role in transforming consumer shopping behaviour. This study investigates the factors influencing consumer buying decisions toward D’Mart products in Bangalore. The research aims to identify key determinants such as price perception, product quality, brand image, store ambience, promotional strategies, and customer service that shape consumer preferences and purchase intentions. A structured questionnaire was administered to 120 respondents across different demographic segments within Bangalore city using a stratified random sampling method. Both descriptive and inferential statistical analyses, including correlation and regression, were applied to evaluate the relationship between demographic variables and buying behaviour. The findings indicate that price affordability and product quality are the most significant influencers of consumer choice, followed by promotional offers and store accessibility. The study also reveals that younger consumers and working professionals are more inclined toward D’Mart’s private-label brands due to perceived value for money and convenience. Customer satisfaction is strongly correlated with store layout, billing efficiency, and staff behaviour, which collectively contribute to brand loyalty. The research contributes to understanding urban retail consumer psychology and offers strategic insights for D’Mart management to enhance customer engagement and retention. By identifying dominant behavioural factors, this study helps develop targeted marketing strategies, optimise store operations, and improve the overall customer experience. Future research could expand to comparative analyses with other retail chains or explore digital shopping trends within India’s organised retail sector.